The Long-Run Determinants of UK Wages, 1860-2004. - Castle, J; Hendry, D (Elsevier, 2009)
As it is almost 50 years since Phillips (1958), we analyze an historical series on UK wages and their determinants. Huge changes have occurred over this long run, so congruence is hard to establish: real wages have risen more than 6 fold, and nominal 500 times; laws, technology, wealth distribution, and social structure are unrecognizably different from 1860. We investigate: wage rates and weekly earnings; real versus nominal wages; breaks over 1860-2004; non-linearities, including Phillips' non-linear response to unemployment; 'trade union power' and unemployment benefits; and measures of excess demand, where workers react more to inflation when it rises.